2022
DOI: 10.1177/0957154x221090631
|View full text |Cite
|
Sign up to set email alerts
|

Maoism and mental illness: psychiatric institutionalization during the Chinese Cultural Revolution

Abstract: This article offers a preliminary analysis of psychiatric treatment during the Chinese Cultural Revolution on the basis of interviews and rare case records obtained from ‘F Hospital’ in southern China. In contrast to the prevailing view of psychiatry during this time, which highlights either rampant patient abuse or revolutionary ideology, we show that psychiatric treatment at this facility was not radically altered by the politics of the Maoist period. Instead, treatments were informed by a predominantly biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is found that the willingness to work of the mental health guards at the local level in China was low [76] . Visiting a psychological counselor may be unsettling, although it is the first step in solving the issue, and there were lots of patient abuse during the Cultural Revolution [77] , [78] . Therefore, people with mental illness are encountering social exclusion, and are limited integration into communities [13] , [16] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the willingness to work of the mental health guards at the local level in China was low [76] . Visiting a psychological counselor may be unsettling, although it is the first step in solving the issue, and there were lots of patient abuse during the Cultural Revolution [77] , [78] . Therefore, people with mental illness are encountering social exclusion, and are limited integration into communities [13] , [16] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Our decision is partially based on realistic considerations. As pointed out by Baum and Lin (2022), research on psychotherapy in Communist China has been plagued by the lack of primary data. 4 Existing research findings have been mostly based on two streams of problematic sources of data: recordings made by foreign visitors who were exceptionally allowed to participate in guided tours in Communist China, and retrospective memoirs mostly produced by individuals who had suffered from the political turmoil.…”
Section: Data and Analytic Strategiesmentioning
confidence: 99%
“…1.There were exceptional cases in which psychiatric institutions operated normally, relatively unaffected by political pressures (Baum & Lin, 2022). …”
mentioning
confidence: 99%